Neuropathological contributions to grey matter atrophy and white matter hyperintensities in amnestic dementia - Diana Ortega-Cruz; Alberto Rabano; Bryan A. Strange (Alzheimer’s Research & Therapy)
Abstract Background Dementia patients commonly present multiple neuropathologies, worsening cognitive function, yet structural neuroimaging signatures of dementia have not been positioned in the context of combined pathology. In this study, we implemented an MRI voxel-based approach to explore combined and independent effects of dementia pathologies on grey and white matter structural changes. Methods In 91 amnestic dementia patients with post-mortem brain donation, grey matter density and white matter hyperintensity (WMH) burdens were obtained from pre-mortem MRI and analyzed in relation to Alzheimer’s, vascular, Lewy body, TDP-43, and hippocampal sclerosis (HS) pathologies. After exploring co-occurrence profiles of these pathologies, voxel-based morphometry was implemented to determine their joint and independent effects on grey matter loss. The impact of these pathologies on WMH burden was then evaluated both in spatial and quantitative combined analyses, using voxel-based and generalized linear models respectively. Results 86.8% of patients in this cohort presented more than one pathology. The combined structural effect of these pathologies was a focal impact on hippocampal grey matter atrophy, primarily driven by HS and Alzheimer’s pathology (family-wise error corrected, p < 0.05), which also exhibited the strongest individual effects (uncorrected, p < 0.001). WMHs, predominant in middle and anterior cerebral portions, were most strongly associated with vascular (T = 2.47, p = 0.017) and tau pathologies (T = 2.09, p = 0.041). Conclusions The mixed associations of these dementia neuroimaging hallmarks are relevant for the fine-tuning of diagnostic protocols and underscore the need for comprehensive pathology evaluations in the study of dementia phenotypes.